(untitled) (BIRDEM Medical Journal, 2013)
Objective: Evaluation of pelvic organs by laparoscopy in infertile patient. Background: Despite of absence of any known risk factor for infertility various studies indicate that there may be abnormalities in pelvic organ in about two-third of the cases, as evidenced by laparoscopic study. Present study was done to have an idea about the problem in a group of patients reporting to specialised centre. Materials and Methods: It was a prospective study which was undertaken in Gynaecology and Obstetric Department at BIRDEM during the period of January 2001 to December 2001. Results: The study group comprised 100 cases of infertile patients of age between 20 to 40 years. Sixty seven percent patients had primary infertility and 33% patients had secondary infertility. Size and shape of uterus was normal in 76% cases and bicornuate uterus was found in 2% cases. Right ovary was normal in 51%patient and left ovary was normal in 53%. Polycystic changes of right ovary were observed in 23% and of left ovary in 22% cases . Right fallopian tube was normal in 71% and left fallopian tube was normal in 69% cases. Patency of right fallopian tube was found in 89%and patency of left fallopian tube was found in 90%. Eleven percent patients were found to have peritubal adhesion on right side and 10% on left side. Pouch of Douglas was found to be normal in 69% cases and 9% cases had adhesion with obliteration. Conclusion: Laparoscopy is an important tool for diagnosing anatomical and pathological abnormalities of internal genital organs which plays a major role in infertility management. For treating infertility, we should give appropriate importance on laparoscopic evaluation of pelvic organs. Birdem Med J 2013; 3(2): 90-93 DOI: http://dx.doi.org/10.3329/birdem.v3i2.17212